Evaluasi Kebijakan dalam Peningkatan Mutu Pendidikan di Indonesia - Amar Syaifullah; Farid Setiawan; Sendi Nurtanti; Avivah Rahma Dini (Jurnal Pendidikan Indonesia (JOUPI), 2023)
Improving the quality of human resources is very much needed in the process of enforcing the education sector in the era of globalization. The teacher is a component of the education system that determines the location of the success of an education. As low as the quality of school resources, the process of teaching and learning activities will continue to be carried out as long as there are educators teaching and students who are learning, then socialization needs to be carried out by the education office to all schools consisting of school principals and educators. Evaluation of educational policies is an activity to find out how educational policies are in accordance with the criteria and have a real impact as expected. The purpose of this study is to understand in evaluating policies in improving the quality of education in Indonesia this type of qualitative descriptive research.